System Parameter Optimization based on Genetic Algorithm - Hu, Haoya (International Journal of Mechanical and Electrical Engineering, 2024)
Genetic algorithm is an algorithm based on the coding strategy and propagation principle of biological evolution. It constructs a universal framework suitable for solving complex system optimization problems. The algorithm is unique in its independence for specific application areas and strong adaptability to different problem types, making it able to effectively deal with extremely challenging problems. Genetic algorithm is especially suitable for global optimization problems and has the ability to jump out of the local optimal solution and search for the global optimal solution. In addition, it supports the definition of complex fitness evaluation functions and can impose constraints on the search space of variables.